Prioritization of network transformers in electrical distribution system by considering social welfare index - A. Prudhvi Krishna; P. Srinivasa Varma; R. B. R Prakash; V. Kiran Babu (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
To supply a meshed distribution system, network transformers are required. When few transformers are not in service, they must be repaired or replaced. A method is proposed for prioritizing the transformers considering the critical loads. Repair or replacement of transformers can be done by giving priority based on risk reduction. By addressing the possibility of network collapse due to failure of the feeder and impacted customers, risk can be predicted where the loads are extremely used at feeders section, network transformers and secondary mains. To select the transformer that needs to be replaced quickly and economically, an algorithm is proposed and it was tested on IEEE test system using GridLAB-D, MATLAB softwares. An index is proposed to give priority to emergency needs like hospitals and water pumping stations. Replacement or repair can be done by prioritizing network transformers incorporating social welfare index.